The impact of cold-water immersion on post-match recovery in trained soccer players: A systematic review and meta-analysis - Veen, J.; Bergh, C.; Cao, Y.; Randers, M. B.; Krustrup, P.; Edholm, P. (Scandinavian Journal of Medicine & Science in Sports, 2026)
Cold-water immersion (CWI) is widely used by elite soccer players to enhance recovery after match play, yet systematic evidence supporting the effectiveness of this intervention is lacking. This systematic review with meta-analysis aimed to evaluate the effects of CWI on the recovery of physical performance, muscle damage, and delayed muscle soreness in trained soccer players after match play. A systematic database search was conducted and inclusion criteria were: (1) peer-reviewed, controlled trials; (2) competitive soccer players; (3) comparison of CWI with control/placebo after match/simulated match-play; (4) at least one of the following outcomes: 20 m sprint, countermovement jump (CMJ), leg strength via maximal voluntary contraction (MVC), creatine kinase (CK) for muscle damage, or delayed onset of muscle soreness (DOMS); and (5) outcome measurements taken 24, 48 or 72 h post-match. Random-effects meta-analyses were performed to calculate standardized mean differences (SMD) with 95% confidence intervals (CI) and prediction intervals (PI). Ten studies met the inclusion criteria. CWI significantly improved recovery of MVC (SMD = 1.02 [95% CI: 0.55 to 1.50; 95% PI: -0.48 to 2.53]) and CMJ (SMD = 0.38 [95% CI: 0.12 to 0.64; 95% PI: -0.39 to 1.15]), while sprint performance remained unaffected (SMD = -0.59 [95% CI: -1.41 to 0.23; 95% PI: -4.14 to 2.95]). CWI reduced CK levels (SMD = -0.77 [95% CI: -1.17 to -0.37; 95% PI: -2.23 to 0.69]) and alleviated DOMS (SMD = -1.04 [95% CI: -1.91 to -0.17; 95% PI: -4.12 to 2.03]). MVC and CK recovery improved consistently across all time points, while DOMS relief was observed at 24 and 72 h post-match. CMJ benefits were only evident at 48 h post-match. However, as the 95% PIs for all outcomes included the null effect, the observed benefits should be interpreted cautiously, as future studies may yield smaller or null effects. Overall, CWI may enhance recovery of muscle strength, reduce muscle damage, and alleviate soreness in trained male and female soccer players, but does not seem to impact sprint performance, and its effect on CMJ is time-dependent.